Intentionally slow concentric velocity resistance exercise and strength adaptations: a meta-analysis - Hermes, M. J.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2023)
Intentionally slow-velocity resistance exercise (ISVRE) is suggested by some to be equally or more effective than fast or traditional velocities for increasing muscular strength. The purpose of this meta-analysis was to assess the effect ISVRE has on strength adaptations compared with faster or traditional velocities, with subgroup analyses exploring age, sex, and training status as confounding factors on the influence of velocity on strength adaptation. Eligible studies (n = 24) were required to be chronic (multiple weeks) randomized or nonrandomized comparative studies using dynamic constant external resistance for training and testing, and pre-post strength assessments. All studies examined healthy individuals (n = 625; fast or traditional n = 306, intentionally slow n = 319). A random-effects meta-analysis indicated a significant (p = 0.05) effect in favor of fast training (effect size [ES] = 0.21, 95% confidence interval [CI] = 0.02-0.41, p = 0.03). Publication bias was noted through trim and fill analysis, with an adjusted effect size estimate of 0.32 (p < 0.001). Subgroup analyses indicated no difference between trained and untrained subjects (QM = 0.01, p = 0.93), and no difference between older and younger subgroups (QM = 0.09, p = 0.77), despite younger favoring faster (ES = 0.23, p = 0.049) and older not favoring either velocity (ES = 0.16, p = 0.46). Subgroup analysis also indicated women favored faster training (ES = 0.95, p < 0.001) in comparison to men (ES = 0.08, p = 0.58). Contrary to some previous reviews, these results indicate that chronic fast or traditional velocity resistance exercise increases muscular strength to a greater degree than ISVRE training. Resistance training velocity must be considered if strength is a desired outcome.